Hubera senjiana is now Huberantha senjiana (Annonaceae) - Muralidharan, Ramachandran; Narasimhan, Duvuru; Balachandran, Natesan (Phytotaxa, 2015)
The genus Hubera Chaowasku in Chaowasku et al. (2012) was established in accordance with strict monophyly based on a molecular phylogenetic analysis and morphological characters; the component species were previously considered members of the polyphyletic genus Polyalthia Blume s.l. (1830 : 68). Chaowasku, however, later felt that the genus name Hubera was too similar to Huberia DC (1828 : 167; Melastomataceae) and asked the nomenclature committee for vascular plants if it should be treated as a later homonym of Huberia DC. (Chaowasku 2013). His request was accepted by the nomenclature committee for vascular plants (Applequist 2014). Subsequently, Chaowasku replaced the generic name Hubera with a new name Huberantha and also made new combinations for all 27 species of that genus (Chaowasku et al. 2015). A new species that was recently published under Hubera (Muralidharan et al. 2015) is here transferred to Huberantha.